2021
DOI: 10.1007/s11695-021-05384-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Same-Day Discharge After Laparoscopic Roux-en-Y Gastric Bypass Using Remote Monitoring

Abstract: Background Shortening of hospital stay to 1 night has not affected the short-term safety of patients undergoing laparoscopic Roux-en-Y gastric bypass (RYGB). Whether the RYGB is feasible in an ambulatory setting (same-day discharge) without overnight hospital stay remains to be answered. We aimed to evaluate the feasibility of same-day discharge after laparoscopic Roux-en-Y gastric bypass (RYGB) using additional live video consultation and remote monitoring. Same-day discharge (SDD) was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
(30 reference statements)
0
24
0
1
Order By: Relevance
“…More recently, several centers started to perform major bariatric operations (RYGB and sleeve gastrectomy (SG)) on a day-case/ambulatory basis with encouraging outcomes [ 14 19 ]. Same-day discharge might reduce costs and nosocomial infections, and improve patients’ satisfaction [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, several centers started to perform major bariatric operations (RYGB and sleeve gastrectomy (SG)) on a day-case/ambulatory basis with encouraging outcomes [ 14 19 ]. Same-day discharge might reduce costs and nosocomial infections, and improve patients’ satisfaction [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A couple of single-center series reported that SDD-RYGG is safe and feasible in selected patients [ 17 , 19 ]. For instance, Leepalao et al performed a retrospective analysis of 362 patients who underwent SDD-RYGB and found no mortalities, 98.1% SDD success, 3.6% readmission, 2.5% complication, and 2.5% reoperation rates [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies show no increase in mortality with same-day discharge of LSG with mixed results on increased morbidity with POD 0 discharge versus POD 1. To our knowledge, there are only four other studies that look at discharging LRYGB on POD 0 [ 20 23 ], and they report a mixed safety profile for same-day discharge of LRYGB. In 2014, Morton et al [ 20 ] reviewed the Bariatric Outcomes Longitudinal Database to determine the safety of same-day discharge of LRYGB, and Inaba et al [ 21 ] used the 2015 Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) database to evaluate the safety of same-day discharge after LRYGB.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies published in 2019 and 2021 by Leepalao et al [ 22 ] and Nijland et al [ 23 ] show that there is no increase in morbidity with same-day discharge after LRYGB. Leepalao et al examined 362 patients and found a readmission rate of 3.59%, and a complication rate of 0.24%, and had 0% mortality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing laparoscopic Roux-en-Y gastric bypass surgery, Nijland et al demonstrated an 88% success rate in same-day discharge by utilizing these monitoring techniques. 8 Same-day discharge patients were remotely monitored for 48 hours after surgery using a medical device measuring vital signs three times a day. Video consultations were performed by a doctor twice a day for two postoperative days.…”
Section: Remote Monitoring Of Patients After Surgerymentioning
confidence: 99%